The first disaster of the Internet age. - Kedrosky, Paul.
Aln Greenspan lit the fuse of the credit crisis when he extolled the revolutionary virtues of the 'Net--and redefined risk and responsibility.
Keywords: Internet; Financial crisis; Credit crisis